2021
DOI: 10.1002/smtd.202001045
|View full text |Cite
|
Sign up to set email alerts
|

RNA m6A Modification Alteration by Black Phosphorus Quantum Dots Regulates Cell Ferroptosis: Implications for Nanotoxicological Assessment

Abstract: Nanosafety is a major concern for nanotechnology development. Evaluation of the transcriptome and the DNA methylome is proposed for nanosafety assessments. RNA m6A modification plays a crucial role in development, disease, and cell fate determination through regulating RNA stability and decay. Here, since black phosphorus quantum dots (BPQDs), among many other types of QDs, increase the global m6A level and decrease the demethylase ALKBH5 level in lung cells, the epitranscriptome is taken into consideration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 54 publications
0
29
0
2
Order By: Relevance
“…A large number of previous studies have found that m 6 A methylation levels can regulate genes involved in the regulation of ferroptosis. Studies have found that m 6 A modification enhances ferroptosis in stellate cells by stabilizing BECN1mRNA to trigger autophagy activation [ 16 ]. Other studies have found that METTL3-mediated m 6 A methylation can stabilize SLC7A11mRNA and accelerate translation, thereby inhibiting ferroptosis and accelerating the proliferation of lung cancer cells [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of previous studies have found that m 6 A methylation levels can regulate genes involved in the regulation of ferroptosis. Studies have found that m 6 A modification enhances ferroptosis in stellate cells by stabilizing BECN1mRNA to trigger autophagy activation [ 16 ]. Other studies have found that METTL3-mediated m 6 A methylation can stabilize SLC7A11mRNA and accelerate translation, thereby inhibiting ferroptosis and accelerating the proliferation of lung cancer cells [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modification methods of mRNA consist of N6-adenine (m 6 A), n1-adenine (m1A), pseudouracil, and 5′-cytosine methylation, of which m6A is the most common [ 10 , 16 ]. These modifications affect the splicing, expression, and translation of mRNA, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering their easy inhalation ability, we used lung cells to further evaluate the bioimpacts of BPQDs and their correlation with m 6 A RNA modification. Surprisingly, the global m 6 A level was increased after BPQD exposure in lung cells, and after the protein expression of m 6 A-related proteins was examined, we further clarified the significant role of ALKBH5 in this event; the expression of “writers” and other “erasers” did not change, but ALKBH5 decreased with BPQD exposure [ 105 ]. Transcriptome and epitranscriptome data have provided evidence of the correlation between the abnormal elevation of total m 6 A levels and the aberrant expression of genes related to ferroptosis involving ER stress, iron homeostasis and iron homeostasis, which has also been verified by evidence of iron overload, lipid peroxidation, glutathione peroxidase 4 (GPX4) downregulation and glutathione (GSH) depletion in vitro.…”
Section: M 6 a Rna Modification Modulates The Bioi...mentioning
confidence: 99%
“…MPNPs improve anti-virus ability in VSV-infected macrophages. TiO 2 -NPs cause cardiac impairment by upregulating the total m 6 A level [ 104 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Figurementioning
confidence: 99%
“…Aberrant m 6 A as crucial drivers of multiple diseases (especially cancers) can provide an epitranscriptomic indicator of cellular responses and pathogenetic effects induced by nanomaterials, of which field remains largely unknown [ 40 – 43 ]. Although several omics-based approaches have been used to assess biological effects of nanomaterials, the epitranscriptomics has rarely been applied in the field of nanosafety evaluations so far [ 44 ]. Therefore, it is of great significance to investigate the nanomaterial-induced epitranscriptomics scenery.…”
Section: Introductionmentioning
confidence: 99%